2013
DOI: 10.1016/j.ijporl.2013.03.031
|View full text |Cite
|
Sign up to set email alerts
|

The effects and outcomes of electrolyte disturbances and asphyxia on newborns hearing

Abstract: Objective To determine the effect of electrolyte disturbances (ED) and asphyxia on infant hearing and hearing outcomes. Study Design We conducted newborn hearing screening with transient evoked otoacoustic emission (TEOAE) test on a large scale (>5,000 infants). The effects of ED and asphyxia on infant hearing and hearing outcomes were evaluated. Result The pass rate of TEOAE test was significantly reduced in preterm infants with ED (83.1%, multiple logistic regression analysis: P<0.01) but not in full-ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 31 publications
1
6
0
2
Order By: Relevance
“…As regards hearing affection, our study showed a statistically significant lower serum Ca and corrected serum Ca in cases with hearing impairment than in cases without hearing impairment (P<0.05).There was no statistically significant difference as regards serum sodium in both groups. This is consistent with both Saha et al [6] and Liang et al [9] and El Mashad et al [10] studies. At Saha et al study, children with nephrosis and hearing impairment had low corrected serum calcium levels (P<0.04).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…As regards hearing affection, our study showed a statistically significant lower serum Ca and corrected serum Ca in cases with hearing impairment than in cases without hearing impairment (P<0.05).There was no statistically significant difference as regards serum sodium in both groups. This is consistent with both Saha et al [6] and Liang et al [9] and El Mashad et al [10] studies. At Saha et al study, children with nephrosis and hearing impairment had low corrected serum calcium levels (P<0.04).…”
Section: Discussionsupporting
confidence: 91%
“…They found that patients with SNHL over 70 db had significantly lower serum sodium and this signifies the role of electrolyte disarray in causing SNHL. On the other hand, Liang et al [9] found no significant effect in cases with hyponatremia.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Ethical problems derived from the use of control groups (with no treatment) and informed consent are eliminated. However, the complexity of mechanisms and organic interactions of perinatal asphyxia, as well as the presence of multiple comorbidities, particularly those of neurological development, cause animal studies to vary in terms of species, injury methods, metabolic approach, and biospecific sample, among other factors, as can be seen in the following table of revised animal models [ 26 , 30 , 61 , 70 , 71 , 159 , 162 , 165 , 166 , 167 , 169 , 170 , 171 , 172 , 173 , 174 , 178 , 179 , 180 , 181 , 182 , 186 , 188 , 189 , 191 , 192 , 193 , 194 , 195 , 196 , 197 ].…”
Section: Scientific Findings Of Perinatal Asphyxia In Animal Models: ...mentioning
confidence: 99%
“…[66][67][68] There is adequate evidence supporting the hypothesis that OAEs are very good prognostic descriptors of the status and recovery of SSNHL. [69][70][71] A 2013 Chinese study by Liang et al 72 correlated the effects of electrolyte disturbances (EDs) and asphyxia in a large newborn sample (>5000 participants), using TEOAEs. The data suggested that EDs have a very important role in the cases which fail to pass the TEOAE tests.…”
Section: Discussionmentioning
confidence: 99%